Carbon sequestration potential of Scenedesmus quadricauda (Turpin) and evaluation on Zebra fish (Danio rerio) - A. Maryshamya; T. Rajasekar; R. Rengasamy (Aquaculture Reports, 2019)
Carbon dioxide sequestration by microalgae is receiving increased attention in alternative impact of increasing CO2 in the atmosphere. For this study, we have chosen three different microalgae such as Chlorococcum humicola, Chlorella vulgaris and Scenedesmus quadricauda were treated with 3 W/m2 UV-B radiation in different time durations (10, 15, 30, 45 and 60 min) and supplemented with bold basal medium. Parameters such as Total Chlorophyll, protein, Carbohydrate, and CO2 fixation rate were determined. Based on the parameters Scenedesmus quadricauda is used for carbon sequestration study. Different concentrations of sodium bicarbonate (0.2%–1%) were supplemented to bold basal medium for carbon utilization it can act as an alternative source of atmospheric CO2. In this maximum amount of chlorophyll content were observed in 0.6% of Sodium bicarbonate. The uttermost amount of CO2 fixation rate and lipid content was recorded at 0.4% sodium bicarbonate concentration. Finally, the result indicated that Scenedesmus quadricauda could be used for CO2 mitigation and having a rich source of polyunsaturated fatty acid. Further urea and glucose in the media positively influence growth and CO2 fixation rate of micro algae. These carbon and PUFA rich microalgae can be used as dietary feed fish usually obtain necessary nutrients via bioaccumulation through the food chain. Thus, this study proves to be an encouraging source of discovery of alternating the dietary source for fish and also helping in carbon utilization process in a natural way. Keywords: Carbon sequestration, Microalgae, Scenedesmus quadricauda, PUFA, CO2 Fixation